2021
DOI: 10.3389/fpls.2021.641501
|View full text |Cite
|
Sign up to set email alerts
|

Plant Availability of Magnesium in Typical Tea Plantation Soils

Abstract: Background and Aims: Magnesium (Mg) fertilizer has been proved to play an important role in improving the yield and quality of tea. However, plant availability of Mg, including its use, efficiency, and quality improvement effects, were highly affected by plant species, soil characteristics (nutritional status, etc.), and Mg status (chemical-available, etc.).Methods: Tea plants were pot-cultivated in 12 typical tea plantation soils amended with and without Mg fertilizer. Exchangeable Mg (Ex-Mg) concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…Higher Mg content in the lower depth can be attributed to leaching in the humid environment. Magnesium leaching in the soil was also observed in other studies including Zhang et al. (2021) and Ng et al.…”
Section: Resultssupporting
confidence: 82%
“…Higher Mg content in the lower depth can be attributed to leaching in the humid environment. Magnesium leaching in the soil was also observed in other studies including Zhang et al. (2021) and Ng et al.…”
Section: Resultssupporting
confidence: 82%
“…A tea plant (Camellia sinensis) is an important leaf-type woody crop, which is mainly distributed in the tropics and subtropics of southern China, accounting for 45.9% of the tea planting area worldwide . Chemical mineral weathering and leaching in humid climates, combined with long-term nitrogen application, result in soil acidification of tea gardens, which ultimately decreases the content of available Mg 2+ . , Up to 70% of tea gardens in south China were generally deficient in Mg, and Mg deficiency was also noticed in some tea-producing countries such as India, Indonesia, and Nigeria. , In terms of the importance of economic growth of C. sinensis, the requirement for Mg nutrition is only after nitrogen and potassium .…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress is another principal concern in horticultural crop production, particularly given ongoing global warming. Recent studies on lemon trees and tea have demonstrated the beneficial effects of Mg 2+ in mitigating the adverse impacts of heat stress ( Du et al., 2021 ; Zhang Q. et al., 2021 ). In a study by Boaretto et al.…”
Section: Impact Of Magnesium On Crop Developmentmentioning
confidence: 99%